PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KUALITAS PEMBELAJARAN AL-QUR'AN HADITS PADA SISWA KELAS VIII MTs. SWASTA YASPEN MUSLIM PEMATANG TENGAH KECAMATAN TANJUNG PURA - Ahmad Fuadi, Usmaidar, Asriniarti (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2022)
The main background of the research problem relates to the importance of increasing the pedagogic competence of Al Qur'an Hadith teachers in carrying out learning activities so that they can improve the quality and student learning outcomes. Increasing pedagogic competence needs to be done by teachers to develop their abilities. Pedagogic competence of teachers can understand students by utilizing the principles of cognitive development of students and teachers can understand the development of students' personality and reflect on it in the learning process. The purpose of this study was to determine the effect of teacher pedagogic competence on the quality of learning Al-Qur'an Hadith in MTs students. Private Yaspen Muslim Pematang Tengah, whether the two variables have a significant relationship. This type of research is a quantitative research. Methods of collecting data by means of observation, interviews, questionnaires and documentation. The population was 114 students were taken as research samples totaling 24 students in MTs. Private Yaspen Muslim Pematang Tengah. Hypothesis testing analysis technique will be used Product Moment correlation formula. The results showed that the influence of teacher pedagogic competence on MTs students. Private Yaspen Muslim Pematang Tengah is good (58%). While the quality of learning the Qur'an hadith on MTs students. Private Yaspen Muslim Pematang Tengah is good (67%). The results of tabulation calculations between the influence of teacher pedagogic competence on the quality of learning Al-Qur'an Hadith in class VIII MTs. Private Yaspen Muslim Pematang Tengah with a moderate or moderate level of significanc